CDC25B Is a Prognostic Biomarker Associated With Immune Infiltration and Drug Sensitivity in Hepatocellular Carcinoma - Zixiang Huang; Liangzhi Xu; Zhengqiang Wu; Xiaofeng Xiong; Linfei Luo; Zhili Wen (International Journal of Genomics)
Cell division cycle 25B (CDC25B), a member of the CDC25 phosphatase family, plays a key role in cell cycle regulation. Studies have suggested its carcinogenic potential in various cancers, but the role of CDC25B in the development of hepatocellular carcinoma (HCC) remains poorly understood. The aim of this study was to clarify the role of CDC25B in HCC using bioinformatics and experiments. CDC25B expression data of HCC cancer tissues and paracancerous normal samples were obtained from The Cancer Gene Atlas (TCGA) and Gene Expression Omnibus (GEO) databases, and the relationship between CDC25B expression and the prognosis and degree of tumor differentiation of HCC patients was analyzed. CDC25B expression was verified in clinical HCC tissue samples using fluorescence quantitative polymerase chain reaction (q-PCR) and protein immunoblotting (Western blot). Gene set enrichment analysis (GSEA) was used to identify signaling pathways enriched in CDC25B expression, and differential genes (DEGs) were used to screen out coexpressed hub genes and construct protein-protein interaction (PPI) networks. 5-Ethynyl-2′-deoxyuridine (EDU) staining was used to compare the proliferation and differentiation ability of the HCC cell line (HCC-LM3) after knockdown of CDC25B. Finally, we investigated the mutation of CDC25B in HCC and the relationship between CDC25B expression and tumor cell infiltration of lymphocytes and some immune checkpoints as well as drug sensitivity. CDC25B was overexpressed in HCC tissues and correlated with poor prognosis and the degree of tumor differentiation in patients with HCC. The GSEA and PPI networks together revealed significantly upregulated signaling pathways, as well as functions, associated with the development of HCC when CDC25B was overexpressed. The EDU assay demonstrated that the ability of cells to differentiate value addedly was markedly reduced following the downregulation of CDC25B expression in HCC-LM3s. CDC25B was also involved in the formation of the tumor microenvironment (TME) and immune processes in HCC, and the high expression of CDC25B made patients less sensitive to some drugs. CDC25B can be used as a biomarker and immunotherapeutic target for poor prognosis and partial drug sensitivity in HCC, providing new ideas for HCC treatment.